Performance Evaluation on PDAM Tirtawening of bandung City Based on Balanced Scorecard Method - Wibowo, Garuda Sade (Journal of Business and Management, 2015)
Abstract— Perusahaan Daerah Air Minum (PDAM) Tirtawening is a local company engaged in the provision of drinking water in the Bandung city. PDAM Tirtawening has not used any method to evaluate their company’s performance.The aim of this study is to design a performance monitoring and evaluate the performance of PDAM Tirtawening from 2011 to 2013 using the Balanced Scorecard method to propose the alternative strategy for them. Results from this study indicate that the performance of PDAM Tirtawening based on the Balanced Scorecard method is bad and under perform. Financial perspective performance have low revenue and  not good recording system. The performance of the customer's perspective in general has been good but its targets too low. In the internal business process perspective, the production and distribution is not efficient and effective. In the perspective of learning and growth have no plan for employee quality growth. The purpose of evaluation is to give the company recommendation for strategy. Keyword—Balanced Scorecard, Performance Evaluation, Business Strategy, Monitoring Dashboard, Local Company, PDAM